OPTIMALISASI BELAJAR MANDIRI TATA PAMONG ( Tinjauan Kritis dan Pengembangan Terhadap Peningkatan Kualitas Sumber Daya Manusia yang Berkarakter) - Trisiana, Anita (UNIVERSITAS SLAMET RIYADI, 2014)
Challenges of Higher Education Management development is closely related to character education into the future of alternative develop competence as part of institutional quality improvement. The character will be a part in the achievement of the competence of lecturers who are able to have a sense of responsibility as a citizen and a responsibility to the environment, according to the intelligence and character, and moreover are very, very important is to be charged to the formation and strengthening of the character of students as part of the development of core competencies cover shows honest behavior, discipline, responsibility, courtesy, caring, confident, patriotic, independent, cooperative, democratic, and creative in interacting with communities surrounding environment. Â Keyword: Optimalization, Self Learning, Character